O impacto da migração no peso corporal : uma revisão - Goulão, Beatriz (2015)
Immigrants may be more vulnerable to obesity as a result of the immigration process. The aim of this article is to summarize current knowledge about the impact of immigration on body mass index (BMI). A systematic review was performed in accordance with PRISMA guidelines through a database search of scientific articles (last updated in August 2014). Thirty-nine articles were included and assessed. Results varied according to ethnic background, country of origin and host country. A consistent positive association between BMI and time since immigration was found among Hispanic, European and African immigrants. Less than half of the studies observed a positive association among Asian immigrants. The quality of the majority of the studies assessed was poor, reflecting a need to improve methodology and concept definition. Immigration appears to have a deteriorative effect on BMI. Underlying causes may include changes in nutrition and physical activity, psychological and social factors, and genetic susceptibility and these aspects should be included as moderator variables in future studies.